Filtering feminisms: Emergent feminist visibilities on Instagram. (March 2022) - Savolainen, Laura; Uitermark, Justus; Boy, John D.
Based on interviews with feminist Instagram users, this article studies emergent feminist visibilities on Instagram through the concept of filtering. Filtering entails both enhancement and subtraction: some feminist sensibilities align with Instagram's interaction order, while others become subdued and remain at the margins of visibility. Taken together, users' filtering practices contribute to the confident and happy image, individualistic streak, and accommodationist cast of popular feminism, while also amplifying feminist politics that affirm the pleasures of visibility and desire. Instagram proves a more challenging environment for feminists seeking to criticize competitive individualism and aesthetic norms. The notion of filtering enriches existing research on how online environments reconfigure feminist politics and problematizes the avowal of feminism in media culture.